Fructus mume Extracts Alleviate Diarrhea in Breast Cancer Patients Receiving the Combination Therapy of Lapatinib and Capecitabine - Xing, Hua; Zhang, Lirong; Ma, Jinshu; Liu, Zhen; Song, Changlong; Liu, Yuxia (Frontiers in Pharmacology, 2018)
Lapatinib and capecitabine have been widely used in the therapy of breast cancer. However, long-term use of lapatinib and capecitabine often causes the most common side effect diarrhea, which limit the medicine use. Fructus mume (F. mume) has been proved to be effective to treat chronic diarrhea with few side effects. The compounds from F. mume were extracted by using an ethanol method. Extracts of F. mume (EFM) were analyzed by HPLC. We investigated the protective effects of EFM on the diarrhea caused by lapatinib and capecitabine. From March 1st, 2016 to June 1st, 2017, 208 breast cancer patients with diarrhea caused by lapatinib and capecitabine were recruited. The patients were evenly assigned into two groups: EG group (the patients took 100 mg EFM daily) and CG group (the patients took placebo daily). The effects of EFM on diarrhea and gastrointestinal symptoms were measured by a semiquantitative method seven-point Likert scale. Overall quality of life was measured by SF-36 questionnaire and Hospital Anxiety and Depression Scale (HADS). The HPLC analysis showed that there were three components in EFM, including citric acid, 5-hydroxymethylfurfural (5-HMF), and chlorogenic acid. Breast cancer types were observed by using Hematoxylin and eosin (H&E) stain. The breast cancer can be divided into leaflet, gland and fibroblast types. Patient age, skin metastases, treatment, and grade 1 diarrhea were signiﬁcant risk factors associated with for grade 2 diarrhea. EFM reduced diarrhea and gastrointestinal symptoms by reducing the average scores of the diarrhea symptom and seven-point Likert scale, and improved life quality of patients significantly by improving SF-36 scores and reducing HADS scores when compared to that in the CG group after 6-week therapy and further 4-week follow-up (P<0.05). EFM may be a potential choice for the diarrhea therapy in breast cancer patients.